Coral sand crumb limestone similar material and preparation method thereof
By using components such as heavy calcium carbonate powder and surfactant, similar materials with density and mechanical parameters close to coral sand chip limestone were prepared, which solved the closed pores and high temperature problems caused by cement hydration in the prior art, and achieved the Simulation of high-connectivity pore structures and true reflection of mechanical properties.
Patent Information
- Application Number
- CN202411249636.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing rock-like materials produce closed pores and high temperatures to cause temperature cracks during cement hydration, which cannot effectively simulate the high-connectivity pore structure and physical and mechanical properties of coral sand chip limestone.
Using the preparation method of coral sand chip limestone similar materials, heavy calcium carbonate powder reduces hydration temperature, surfactant reduces surface tension, sodium alginate thickener increases foam stability, and manufactures through specific ratios and process processes. Foam concrete with high porosity and connectivity.
The prepared material density and mechanical parameters are close to the real coral sand chip limestone, which meets the research needs of multiple disciplines, solves the differences in the mechanical properties of existing materials in simulating coral sand chip limestones, and provides a more accurate physical and mechanical model. .
Smart Images

Figure CN119263875A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of geotechnical engineering, and in particular to a coral sandstone-like material and a preparation method and application thereof. Background Art
[0002] As an important rock type in the marine geological environment, reef limestone has unique physical and chemical properties. Its structure, composition and formation process make reef limestone have significant research value in geology, marine science and other fields. With the continuous development of marine engineering, the application of reef limestone in engineering geology, geotechnical engineering and other fields is becoming more and more extensive. However, due to the difficulty of mining and processing reef limestone and its limited resources, the direct use of reef limestone for scientific research or engineering applications may be subject to certain restrictions.
[0003] Rock-like materials are widely used in geotechnical engineering as a simulation and replacement of the physical and mechanical properties of natural rocks. At present, most rock-like materials are composed of barite powder, quartz sand, cement, gypsum and other materials. However, the pores formed by the heat release of cement hydration are mostly closed pores, and the heat released during the hydration process will cause the temperature to rise. The heat accumulates inside the sample for a long time and is not easy to dissipate, thus forming a large temperature difference and temperature stress, causing temperature cracks in the sample. This not only distorts the pore structure of the reef limestone with high connectivity simulated by the similar material, but also causes differences in the physical and mechanical properties of the reef limestone simulated by it. Summary of the invention
[0004] The purpose of the present invention is to provide a coral sandstone similar material and its preparation method and application. The use of heavy calcium carbonate powder can alleviate the cracking of concrete caused by temperature; the surfactant used in the foaming agent has a low surface tension; the addition of salt can make the foam wall thinner, etc., to provide a preparation method and application of coral sandstone similar material. The measured dry density of coral sandstone is 1.03 ~ 1.12g / cm 3 , saturation density is 1.60 ~ 1.68g / cm 3 The porosity is 58.1 ~ 69.6%, the uniaxial compressive strength is 6.57 ~ 10.55MPa, and the tensile strength is 1.46 ~ 2.26MPa. The density and mechanical parameters of this similar material are close to those of the real coral sandstone, and this similar material can be used to simulate coral sandstone for related experimental research.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: A coral sandstone-like material, the coral sandstone-like material is composed of the following components in parts by weight: calcareous sand A 1. Heavy calcium carbonate powder Bgypsum C Cement D 1. Water E Cement foaming agent F Borax G 3. Gypsum retarder H share, B = 0 ~ A , D = C ~ 1.5 C , E = 0.125( A + B ) + 0.6( C + D ) + 50 F , G = 0.004 D , H =0.002 C , A + B + C + D = V, 1.5~2.5, is the dry density of coral sandstone, and V is the volume of coral sandstone sample (cylindrical sample with a diameter of 50 mm and a height of 100 mm).
[0006] Preferably, the cement foaming agent is added in an amount of F = V ,in: is the density of calcareous sand, is the density of heavy calcium carbonate powder, is the density of gypsum, is the density of cement, is the water density, It is the density of cement foaming agent after dilution of 50 times. In particular, considering that the foam may break and lose during the mixing process, the cement foaming agent loss coefficient is defined. ∈ (1.5 ~ 2).
[0007] Preferably, the foaming agent is made of the following raw materials in parts by weight: a part of foaming agent, b part of foam stabilizer, c part of flocculant, d part of thickener, e part of preservative and f part of water; wherein a:b:c:d:e:f =(150-250):(15-25):(2-4):(0.5-1.5):(1-2):(410-430), further preferably, a:b:c:d:e:f = 200: 20 : 3 : 1 : 1.5 : 420.
[0008] More preferably, the foaming agent is sodium fatty alcohol polyoxyethylene ether carboxylate (AEC); the foam stabilizer is alkyl polyglycoside (APG); the flocculant is Polyacrylamide (PAM); the thickener is sodium alginate (SA); and the preservative is casein.
[0009] Preferably, the borax is borax decahydrate with a density of 1.72 g / cm 3 ; Gypsum retarder is a polymerized amino acid type high-efficiency and environmentally friendly gypsum retarder. A method for preparing a coral sandstone-like material comprises the following steps: 1) Preparation of cement foaming agent: add water, then add foaming agent, heat, stir evenly to form foaming liquid; then add foam stabilizer, stir evenly, then add flocculant, preservative and thickener in sequence, stir evenly, and obtain cement foaming agent; 2) Weigh the calcareous sand, heavy calcium carbonate powder, gypsum, cement, water, cement foaming agent, borax and gypsum retarder according to the proportion; 3) Mark the height V where the volume of the mixing container is represented; 4) Stir the cement foaming agent and water until the foam is cloud-like to obtain a foamed foaming agent; 5) Stir the weighed calcareous sand, heavy calcium carbonate powder, gypsum, cement, borax and gypsum retarder to prepare a mixed powder; pour the weighed borax and gypsum retarder into water and stir to obtain a borax gypsum retarder solution; 6) Stir the prepared mixed powder, borax gypsum retarder solution and water to obtain a mixed powder; 7) Add the foamed foaming agent to the mixed powder being mixed in step 6), stir thoroughly, and expand the volume. When the height expands to the V mark, stop adding the foaming agent; 8) Pour the mixed materials into the mold and shake well; 9) After the material solidifies, it is demolded and cured to obtain a coral sandstone-like material.
[0010] Preferably, in step 1), a foaming agent is added and heated to 25-35° C., and stirred evenly to form a foaming liquid.
[0011] Preferably, in step 9), the material is demoulded after solidification and cured at 20-30°C and humidity ≥80% for 25-30 days, preferably for 28 days.
[0012] The coral limestone similar material or the coral limestone similar material prepared by the method is used in the physical and mechanical model of coral limestone. Compared with the prior art, the present invention has the following beneficial effects: 1. The coral sandstone similar material provided by the present invention has properties including density (1:1 similarity) and basic mechanical parameters similar to those of real coral sandstone after being manufactured, can meet the needs of various disciplines, and conform to the requirements of geotechnical engineering physical and mechanical model test technology.
[0013] 2. The raw materials of the similar materials proposed in the present invention are widely available, low in cost, simple in preparation method, easy to process, meet the technical requirements of geotechnical engineering physical and mechanical model tests, and have wide applicability.
[0014] 3. The heavy calcium carbonate powder (CaCO 3 ) The following characteristics: ① With silicate cement clinker C 3 After S reaction, CaCO 3 CSH hydrates are generated on the particle surface (and C 3 S hydration with CaCO 3 The fineness and dosage of the mixture are increased, thereby reducing the C 3 The hydration temperature of S. ② Ca(OH) in cement 2 Easy to attach to CaCO 3 The particle surface reduces the ion concentration in the liquid phase, C 3 The ions on the surface of S particles migrate into the solution, thus accelerating the C 3 The present invention utilizes its characteristics to achieve the purpose of improving the high-temperature cracking phenomenon caused by the heat release of silicate cement hydration.
[0015] 4. When the foaming agent selected by the present invention is dissolved in water, the hydrophobic groups tend to escape from the water phase and gather together, while the hydrophilic groups remain in the water phase. This special molecular arrangement will form a directional arrangement at the interface, change the properties of the interface, reduce the interfacial energy, and thus significantly reduce the surface tension; in addition, these molecules can effectively break the hydrogen bond network between water molecules, further weaken the interaction between water molecules, and also help to reduce the surface tension. In the case of low surface tension, bubbles are more likely to connect and merge with each other, mainly because of the following points: On the one hand, the surfactant reduces the surface tension of the gas-liquid interface, making it easier for bubbles to form and exist stably. When multiple bubbles are close, due to the reduction in surface tension, the interfacial energy between the bubbles is relatively small, and the resistance to overcome the interfacial energy for connection and fusion is also small. On the other hand, the film formed by the surfactant at the gas-liquid interface has certain flexibility and deformability. When the bubbles contact each other, this deformable film can be deformed and adapted to each other more easily, promoting the connection and fusion between the bubbles. Moreover, since calcareous sand is mostly in the shape of flat particles and has an uneven surface, the distribution of bubbles attached to its surface is more random. At the same time, the distribution of surfactant molecules on the surface of the bubbles is not absolutely uniform, which may also lead to local weak points. Since the surface of calcareous sand is uneven and the shapes of the bumps are mostly sharp, the bubbles are easier to connect and merge with each other at these locations, thus making similar materials achieve the effect of different pore sizes and high connectivity.
[0016] 4. The thickener used in the present invention is sodium alginate (SA), which is a linear high molecular polymer composed of β-D-mannuronic acid and α-L-guluronic acid connected by β-1,4-glycosidic bonds and has a large number of carboxylic acid groups. When sodium alginate is added to cement paste, the carboxylic acid groups on its molecular chain can combine with calcium ions in the cement paste through ionic bonds to form a physical adsorption layer. + Ions are incorporated into the foaming agent solution, competing with the foaming agent molecules for water molecules, reducing the interaction between the foaming agent molecules and water molecules, thereby increasing the surface tension of the solution. In order to maintain the stability of the foam, the liquid film will become thinner to reduce the surface area and energy of the foam film. Therefore, the liquid on the foam wall is lost, further promoting the connection or fusion between bubbles.
[0017] 5. The compressive and tensile strengths of the present invention meet the mechanical performance requirements of reef limestone at multiple geometric scales such as 1 / 15, 1 / 25, and 1 / 50, and the scope of application of reef limestone model experiments is wider than that of other products at this stage; in particular, the composition of reef limestone is greater than or equal to 90% CaCO 3 The aggregate of the present invention only contains calcareous sand and heavy calcium carbonate powder (whose main component is also CaCO 3 ), and therefore can better reflect the physical and mechanical properties of the reef limestone parent rock.
[0018] 6. The present invention uses plant and animal bases as components of the foaming agent, and provides the proportion of each component and its preparation method. The pores formed by the foam have the characteristics of high connectivity, uneven distribution and irregular shape compared with the pores formed by other foaming agents at present, which solves the shortcomings of the current porous similar materials with rounded and uniform pore shapes, and is closer to the actual irregular and connected pore structure of reef limestone.
[0019] 7. The method of adding foaming agent to foam concrete in the present invention is different from other methods at present. At present, the method of adding foaming agent is to add it by portion, without considering the foam breakage loss caused by the concrete mixing process. The present invention adds foaming agent by volume, solves the problem of foam loss during the mixing process, and makes the porosity of the prepared similar material more accurate and closer to the actual situation of the original reef limestone rock.
[0020] 8. The present invention not only satisfies the similarity of compressive strength of reef limestone, but also satisfies the similarity of tensile strength. At present, other similar materials of reef limestone only meet the similarity of compressive strength of reef limestone. Therefore, the present invention fills the gap of the dissimilarity of tensile strength of similar materials of reef limestone at present, making the simulation of the actual mechanical properties of reef limestone more realistic and reliable. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Comparison of water absorption and dyeing effects between Example 2 and Comparative Example 2; Figure 2 Comparative Example 3 water absorption dyeing effect. DETAILED DESCRIPTION
[0022] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Sodium fatty alcohol polyoxyethylene ether carboxylate (AEC); the foam stabilizer is alkyl polyglycoside (APG); the flocculant is Gather Acrylamide (PAM); the thickener is sodium alginate (SA); and the preservative is casein.
[0024] The measured data of the coral sandstone limestone original rock (cylindrical sample with a diameter of 50 mm and a height of 100 mm) are shown in Table 1: Table 1 Physical and mechanical data of coral sandstone
[0025] The preparation method of the cement foaming agent in Examples 1-3 and Comparative Examples 1 and 3 is as follows: AEC:APG:PAM:SA:casein:water in the cement foaming agent of the examples is 200:20:3:1:1.5:420. The steps are as follows: first add water into a reaction container (beaker), then add a foaming agent, heat to 30°C, stir evenly, and form a foaming liquid; then, add a foam stabilizer into the beaker, stir evenly, and then add a flocculant, a preservative and a thickener in sequence, stir evenly, and obtain the obtained product.
[0026] All experimental methods were carried out in accordance with “SL264-2001 Rock Test Procedures for Water Conservancy and Hydropower Projects”.
[0027] The method of water absorption and dyeing test is to measure according to the free water absorption method in the specification: first put the sample into the water tank, first fill the ink to 1 / 4 of the height of the sample, then fill the ink to 1 / 2 and 3 / 4 of the height of the sample every 2 hours, and immerse the sample completely after 6 hours. After the sample is fully immersed in the ink and freely absorbs water for 48 hours, take out the sample and split it in half to observe the dyeing situation.
[0028] The sample saturation is carried out according to the vacuum saturation method in the specification, and the density after saturation is the saturated mass divided by the sample volume.
[0029] The porosity is equal to the volume reduced by the liquid in the vacuum saturation method divided by the volume of the sample after saturation.
[0030] The uniaxial compressive strength is determined by a uniaxial compression test.
[0031] The uniaxial tensile strength was determined by the Brazilian splitting test.
[0032] Example 1 (1) The coral sandstone-like material is composed of the following components in parts by weight: A Calcium sand, B= 0.43 A 1 part heavy calcium carbonate powder, C gypsum, D= C Cement, 2.5, the specific addition amount of each component is shown in Table 2, and its physical and mechanical data are shown in Table 3.
[0033] Table 2 Similar material composition table
[0034] (2) Water: 55.80g (water for aggregate and cementitious material) + 100g (2g foaming agent, dilution factor is 50); Borax: 0.098g; Gypsum retarder: 0.073g.
[0035] (3) A preparation method comprising the following steps: first adding water and then adding a foaming agent into a reaction container (beaker), heating to 30°C, and stirring evenly to form a foaming liquid; then, adding a foam stabilizer into the beaker, stirring evenly, and then adding a flocculant, a preservative and a thickener in sequence, stirring evenly to obtain a foaming agent. Weigh calcareous sand, heavy calcium carbonate powder, gypsum, cement, water, cement foaming agent, borax, and gypsum retarder according to the proportion; mark the height of the mixing container indicating the volume as V; stir the weighed cement foaming agent with the required part of water until the foam is cloud-like, and store it for later use; stir the weighed calcareous sand, heavy calcium carbonate powder, gypsum, and cement to make a mixed powder; pour the prepared mixed powder and the required water into the mixing container for stirring; add the foamed foaming agent to the mixed material being mixed, stir it with the mixed material fully, and expand the volume, and stop adding the foaming agent when the height expands to the V mark; pour the mixed material into the mold and shake it well; demould the material after solidification, and cure it for 28 days under the conditions of 25℃ and humidity ≥80% to obtain a similar material. The physical and mechanical data of the prepared similar material are shown in Table 3.
[0036] Table 3 Physical and mechanical data of similar materials (average value)
[0037] (4) The similar material obtained meets the requirements of similar materials under the conditions of density of 1:1 and geometric scale of 1 / 50.
[0038] Comparative Example 1 (1) A Calcium sand, B= 0.43 A 1 part heavy calcium carbonate powder, C gypsum, D=C Cement, 0.5, the specific addition amount of each component is shown in Table 4, and its physical and mechanical data are shown in Table 5.
[0039] Table 4 Similar material composition table
[0040] (2) Water: 94.52g (water for aggregate and cementitious material) + 100g (2g foaming agent, dilution factor is 50); Borax: 0.285g; Gypsum retarder: 0.143g.
[0041] (3) A preparation method comprising the following steps: first adding water and then adding a foaming agent into a reaction container (beaker), heating to 30°C, and stirring evenly to form a foaming liquid; then, adding a foam stabilizer into the beaker, stirring evenly, and then adding a flocculant, a preservative and a thickener in sequence, stirring evenly to obtain a foaming agent. Weigh calcareous sand, heavy calcium carbonate powder, gypsum, cement, water, cement foaming agent, borax, and gypsum retarder according to the proportion; mark the height of the mixing container indicating the volume as V; stir the weighed cement foaming agent with the required part of water until the foam is cloud-like, and store it for later use; stir the weighed calcareous sand, heavy calcium carbonate powder, gypsum, and cement to make a mixed powder; pour the prepared mixed powder and the required water into the mixing container for stirring; add the foamed foaming agent to the mixed material being mixed, stir it with the mixed material fully, and expand the volume, and stop adding the foaming agent when the height expands to the V mark; pour the mixed material into the mold and shake it well; demould the material after solidification, and cure it for 28 days under the conditions of 25℃ and humidity ≥80% to obtain a similar material. The physical and mechanical data of the prepared similar material are shown in Table 5.
[0042] Table 5 Physical and mechanical data of similar materials (average value)
[0043] (4) The uniaxial compressive strength and uniaxial tensile strength of similar materials produced under this ratio are too large to meet the similarity ratio.
[0044] Example 2 (1) A Calcium sand, B= 0.25 A 1 part heavy calcium carbonate powder, C gypsum, D= C Cement, 2. The specific addition amounts of the components are shown in Table 6, and the physical and mechanical data are shown in Table 7.
[0045] Table 6 Similar material composition table
[0046] (2) Water: 23.185g (water for aggregate and cementitious material) + 100g (2g foaming agent, dilution factor is 50); Borax: 0.114g; Gypsum retarder: 0.086g.
[0047] (3) A preparation method comprising the following steps: first adding water and then adding a foaming agent into a reaction container (beaker), heating to 30°C, and stirring evenly to form a foaming liquid; then, adding a foam stabilizer into the beaker, stirring evenly, and then adding a flocculant, a preservative and a thickener in sequence, stirring evenly to obtain a foaming agent. Weigh calcareous sand, heavy calcium carbonate powder, gypsum, cement, water, cement foaming agent, borax, and gypsum retarder according to the proportion; mark the height of the mixing container indicating the volume as V; stir the weighed cement foaming agent with the required part of water until the foam is cloud-like, and store it for later use; stir the weighed calcareous sand, heavy calcium carbonate powder, gypsum, and cement to make a mixed powder; pour the prepared mixed powder and the required water into the mixing container for stirring; add the foamed foaming agent to the mixed material being mixed, stir it with the mixed material fully, and expand the volume, and stop adding the foaming agent when the height expands to the V mark; pour the mixed material into the mold and shake it well; demould the material after solidification, and cure it for 28 days under the conditions of 25℃ and humidity ≥80% to obtain a similar material. The physical and mechanical data of the prepared similar material are shown in Table 7.
[0048] Table 7 Physical and mechanical data of similar materials (average value)
[0049] (4) The similar material obtained meets the requirements of similar materials with a density of 1:1 and a geometric scale of 1 / 25.
[0050] Comparative Example 2 The foaming agent in Example 2 was replaced by Legao TM 2258 cement foaming agent (manufacturer: Shandong Yousuo Huagong Technology Co., Ltd.), and the obtained material and the material in Example 2 were subjected to water absorption and dyeing treatment, and the effect after dyeing was compared. Figure 1 shown. Depend on Figure 1 It can be seen that the material made by ordinary foaming agent is unevenly dyed, indicating that some of the pores formed are in a closed state, so the connectivity is low, while the material prepared in Example 2 is dyed through the inside and outside, indicating that the pore connectivity is better.
[0051] Comparative Example 3 (1) A Quartz sand, B= 0.43 A 1 part barite powder, C gypsum, D= C Cement, The specific addition amounts of each component are shown in Table 8, and the physical and mechanical data are shown in Table 9.
[0052] Table 8 Similar material composition table
[0053] (2) Water: 23.185g (water for aggregate and cementitious material) + 100g (2g foaming agent, dilution factor is 50); Borax: 0.114g; Gypsum retarder: 0.086g.
[0054] (3) A preparation method comprising the following steps: first adding water and then adding a foaming agent into a reaction container (beaker), heating to 30°C, and stirring evenly to form a foaming liquid; then, adding a foam stabilizer into the beaker, stirring evenly, and then adding a flocculant, a preservative and a thickener in sequence, stirring evenly to obtain a foaming agent. Weigh quartz sand, barite powder, gypsum, cement, water, cement foaming agent, borax, and gypsum retarder according to the proportion; mark the height V on the mixing container to indicate the volume; stir the weighed cement foaming agent with the required amount of water until the foam is cloud-like, and store it for later use; stir the weighed quartz sand, barite powder, gypsum, and cement to make a mixed powder; pour the prepared mixed powder and the required water into a mixing container for stirring; add the foamed foaming agent to the mixture being mixed, stir it thoroughly with the mixture, and expand the volume. When the height expands to the V mark, stop adding the foaming agent; pour the mixed material into the mold and shake it well; demould the material after solidification, and cure it at 25°C and humidity ≥80% for 28 days to obtain a similar material. The physical and mechanical data of the prepared similar material are shown in Table 9. Its water absorption and dyeing effect is as follows Figure 2 shown.
[0055] Table 9 Physical and mechanical data of similar materials (average value)
[0056] (4) The uniaxial compressive strength and uniaxial tensile strength of similar materials produced under this ratio are too large, and the pore connectivity is poor, which cannot meet the requirements. Compared with calcareous sand, quartz sand particles are usually more regular in shape and have a smoother surface. Regularly shaped particles help to achieve a more uniform stress distribution in concrete, while the smooth surface helps to improve the bonding between the particles and the cement paste, which makes the compressive and tensile strength of the material too high. The temperature of barite powder during hydration is higher than that of heavy calcium powder cement, and the material solidifies faster, resulting in insufficient time for the bubbles to fuse and connect, resulting in poor pore connectivity.
[0057] Example 3 (1) A Calcium sand, B= 0.25 A 1 part heavy calcium carbonate powder, C gypsum, D=C Cement, 1.5, the specific addition amounts of the components are shown in Table 6, and the physical and mechanical data are shown in Table 4.
[0058] Table 6 Similar material composition table
[0059] (2) Water: 67.41 g (water for aggregate and cementitious material) + 100 g (2 g foaming agent, dilution factor is 50); Borax: 0.171 g; Gypsum retarder: 0.086 g.
[0060] (3) A preparation method comprising the following steps: first adding water and then adding a foaming agent into a reaction container (beaker), heating to 30°C, and stirring evenly to form a foaming liquid; then, adding a foam stabilizer into the beaker, stirring evenly, and then adding a flocculant, a preservative and a thickener in sequence, stirring evenly to obtain a foaming agent. Weigh calcareous sand, heavy calcium carbonate powder, gypsum, cement, water, cement foaming agent, borax, and gypsum retarder according to the proportion; mark the height of the mixing container indicating the volume as V; stir the weighed cement foaming agent with the required part of water until the foam is cloud-like, and store it for later use; stir the weighed calcareous sand, heavy calcium carbonate powder, gypsum, and cement to make a mixed powder; pour the prepared mixed powder and the required water into the mixing container for stirring; add the foamed foaming agent to the mixed material being mixed, stir it with the mixed material fully, and expand the volume, and stop adding the foaming agent when the height expands to the V mark; pour the mixed material into the mold and shake it well; demould the material after solidification, and cure it for 28 days under the conditions of 25℃ and humidity ≥80% to obtain a similar material. The physical and mechanical data of the prepared similar material are shown in Table 7.
[0061] Table 7 Physical and mechanical data of similar materials (average value)
[0062] (4) The similar material prepared meets the requirements of similar materials with a density of 1:1 and a geometric scale of 1 / 15.
[0063] The technical solution of the present invention is explained through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above specific embodiments to be implemented. Any improvements made by technicians in the relevant field based on the present invention, or equivalent replacement of the materials selected by the present invention, etc., fall within the scope of protection of the patent.
Claims
1. A coral sandstone-like material, characterized in that: The coral sandstone-like material is composed of the following components in parts by weight: calcareous sand A 1. Heavy calcium carbonate powder B gypsum C Cement D 1. Water E Cement foaming agent F Borax G 3. Gypsum retarder H share, B = 0 ~ A , D = C ~ 1.5 C , E = 0.125( A + B ) + 0.6( C + D ) +50 F , G = 0.004 D , H = 0.002 C , A + B + C + D = V, 1.5~2.5, is the dry density of coral sandstone, and V is the volume of coral sandstone sample.
2. The coral sandstone-like material according to claim 1, characterized in that: The amount of cement foaming agent added F = V ,in: is the density of calcareous sand, is the density of heavy calcium carbonate powder, is the density of gypsum, is the density of cement, is the water density, The density of cement foaming agent after dilution. In particular, considering that the foam may break and lose during the mixing process, the cement foaming agent loss coefficient is defined as ∈ (1.5 ~ 2).
3. The coral sandstone-like material according to claim 1, characterized in that: The foaming agent is made of the following raw materials in parts by weight: a part of foaming agent, b part of foam stabilizer, c part of flocculant, d part of thickener, e part of preservative and f part of water; wherein a:b:c:d:e:f =(150-250):(15-25):(2-4):(0.5-1.5):(1-2):(410-430), preferably, a: b:c:d:e:f = 200 : 20 : 3 : 1 : 1.5 :
420.
4. The coral sandstone-like material according to claim 3, characterized in that: The foaming agent is sodium fatty alcohol polyoxyethylene ether carboxylate; the foam stabilizer is alkyl glycoside; the flocculant is polyacrylamide; the thickener is sodium alginate; and the preservative is casein.
5. The coral sandstone-like material according to claim 1, characterized in that: The borax is borax decahydrate; the gypsum retarder is a polymerized amino acid gypsum retarder.
6. A method for preparing coral sandstone-like material according to claim 1, characterized in that: The steps include: 1) Preparation of cement foaming agent: add water, then add foaming agent, heat, stir evenly to form foaming liquid; then add foam stabilizer, stir evenly, then add flocculant, preservative and thickener in sequence, stir evenly, and obtain cement foaming agent; 2) Weigh the calcareous sand, heavy calcium carbonate powder, gypsum, cement, water, cement foaming agent, borax and gypsum retarder according to the proportion; 3) Mark the height V where the volume of the mixing container is represented; 4) Stir the cement foaming agent and water to foam until the foam is cloud-like, thereby obtaining a foamed foaming agent; 5) Stir the weighed calcareous sand, heavy calcium carbonate powder, gypsum and cement to make a mixed powder; pour the weighed borax and gypsum retarder into water and stir to obtain a borax gypsum retarder solution; 6) Stir the prepared mixed powder, borax gypsum retarder solution and water to obtain a mixed powder; 7) Add the foamed foaming agent to the mixed powder being mixed in step 6), stir thoroughly, and expand the volume. When the height expands to the V mark, stop adding the foaming agent; 8) Pour the mixed materials into the mold and shake well; 9) After the material solidifies, it is demolded and cured to obtain a coral sandstone-like material.
7. The method for preparing coral sandstone similar material according to claim 6, characterized in that: In step 1), add a foaming agent and heat to 25-35°C, stir evenly to form a foaming liquid.
8. The method for preparing coral sandstone similar material according to claim 6, characterized in that: In step 9), the material is demoulded after solidification and cured for 25-30 days at 20 ~ 30℃ and humidity ≥80%.
9. Application of the coral limestone similar material described in any one of claims 1 to 5 or the coral limestone similar material prepared by the method described in any one of claims 6 to 8 in the physical and mechanical model of coral limestone.